Part-through fracture toughness (KIe) and crack-tip opening displacement (CTOD) of welded joints of AA2014-T6 at low temperatures. (October 2015) - Pan, Qinyan; Huang, Chuanjun; Li, Laifeng
Highlights: We investigate KIe and CTOD ( δm ) of welded joints of AA20l4-T6 at 77 K and 4.2 K. Results demonstrate reduction of fracture resistance of weld metal and fusion zone. Precipitations and inclusions at weld metal and fusion zone were observed. Fractographic results explain reduction of fracture resistance at low temperatures. Abstract: The part-through fracture toughness ( KIe ) and crack-tip opening displacement (CTOD, δm ) of welded joints of aluminum alloy (AA) 20l4-T6, including the weld metal, the fusion zone (FZ), the heat-affected zone (HAZ), and the base material, were investigated at both liquid nitrogen temperature and liquid helium temperature with surface-crack tension (SCT) specimen and single-edge-notched bend (SENB) specimen respectively. Results indicate a conventional fusion welding process leads to formation of second-phase precipitations and inclusions, which cause significant reduction of fracture resistance at the weld metal and the FZ by fractographic analyses of fractured surface.